Reducing the dynamic errors of coordinate measuring machines - Dong, Chensong; Zhang, C.; Wang, B.; Zhang, G. (American Society of Mechanical Engineers, 2003)
Coordinate measuring machines (CMMs) are already widely utilized as measuring tools in the modern manufacturing industry. Fast and accurate probing is the current trend for the next generation of CMMs. However, measuring velocity of CMM applications are limited by dynamic errors that occur in CMMs. In this paper, the dynamic errors of coordinate measuring machines are analyzed theoretically and experimentally. The limited stiffness of air bearings were found to cause dynamic errors due to the existence of Abbe's offsets. The characteristics of the air bearings used on CMMs were modeled by the finite element analysis (FEA). The load capacity and stiffness of the air bearings were computed. Using this model, the dynamic errors of the CMM were reduced through revising the air bearing design. To verify the effectiveness of this approach, the performance of the air bearings was tested both statically and dynamically. The results show that the dynamic errors can be significantly reduced.